Effect of feedback induced emotional states on divergent thinking: The mediation role of response inhibition and the moderation role of encoding style - Lin, Lin; Khalil, Radwa (Marconi Institute for Creativity Conference 2021, 2021)

How social media platforms enhance user engagement in organizational contexts: A systematic literature review - Lin, Lin; Van Zoonen, Ward; Koehnlein, Christian; Moser, Klaus (58th Hawaii International Conference on System Sciences, 2025)
Companies use both organization-specific (internal) and public social media platforms to enable interactions between their employees and customers. However, continued user engagement on these platforms often proves challenging. This study reviews factors influencing user engagement in organizational contexts. Technological features, individual characteristics, and organizational factors are examined. A systematic literature review identified, analyzed, and discussed 39 research papers. The results show that all three groups of determinants influence user engagement. In the internal organizational context, mobile platform availability and management support play a significant role. In the marketing context, platform features, individual motivations, and types of content are essential. Increased user engagement can positively affect employees’ performance and customers’ purchase intention, so the continued management and use of social media platforms are critical to a company's succes
Keywords: organizational social media; user engagement; technological features; individual characteristics; organizational factors

Introducing a gamification element in enterprise collaboration platforms: Only a flash in the pan or a lasting effect? - Stojko, Laura; Lin, Lin; Soucek, Roman; Moser, Klaus; Koch, Michael (ECSCW 2024 Exploratory Papers and Notes, 2024)
Enterprise collaboration platforms are expected to facilitate effective information exchange by supporting employee sociability, i.e., finding communication partners and building common ground. However, they often suffer from low user engagement requiring the implementation of additional design elements to encourage user participation. Though previous research found evidence for the effectiveness of introducing new features, in particular gamification elements, to such platforms, the question remains whether it represents more than a flash in the pan and creates some sustainable effects over time. Therefore, the current longitudinal quasi-experimental field study investigates the effectiveness of introducing one exemplary gamification element, a progress bar to encourage profile completion, as a new feature within a digital collaboration platform in a large public sector organization across time. We collected data before (t1 – t3) and after (t4 – t6) implementation of the progress bar. We analyzed the data using linear mixed-effects models, enabling the assessment of time effects and interaction effects of time and progress bar implementation. In fact, profile completion rates increases over time, and introducing a progress bar significantly impacted users’ profile completion behavior. More importantly, we found both short-term effects and, after an interim decline, a sustainable change in user behavior after the progress bar implementation over time. Thus, this study presents quantitative evidence of the long-term effectiveness of introducing a gamification element in enterprise collaboration platforms over time.<br
Keywords: enterprise collaboration platforms; user profiles; profile completion; gamification; mixed-effects

Response inhibition partly mediates the relationship between emotional states and creative divergent thinking - Khalil, Radwa; Lin, Lin; Karim, Ahmed A.; Godde, Ben (Creativity Research Journal, 2023)
Why can some people generate outstanding creative ideas despite receiving frustrating feedback? Although previous studies highlighted the effects of emotional states on creativity, the interactions between specific psychophysiological emotional parameters or affective states and response inhibition (RI) on creativity remain elusive. Therefore, with this study, we aimed to investigate whether RI mediates the effects of emotional states on creative thinking, specifically divergent thinking (DT), while participants receive frustrating or encouraging feedback. We induced positive and negative affect and psychophysiological arousal (PA) by manipulating feedback on performing a go/no-go task (GNGT), one of the standardized tasks for measuring RI. In other words, we provided participants with artificial feedback on GNGT to induce either frustration following (a negative emotional state) or a feeling of success (a positive emotional state). After receiving the manipulated feedback, participants performed the alternative uses task (AUT), a classical test for measuring DT. Subjective affective states were assessed using the Positive and Negative Affect Scale-Expanded Form (PANAS-X). During AUT, PA was measured through skin conductance (SC) and heart rate variability (HRV). Our data revealed that RI mediates the effect of negative affect and fatigue and enhanced PA (measured through HRV) on DT. Moreover, positive affect and PA (measured through SC) directly enhanced the three indices of DT (fluency, originality, and flexibility). Concerning the measurement of HRV, the application of time-domain HRV analyses was superior to that of frequency-domain HRV analyses. Notably, gender had strong direct and indirect effects on fluency and flexibility but not originality. In conclusion, our results suggest distinct mechanisms for modulatory effects of specific emotional states and associated psychophysiological on divergent creative thinkin
Keywords: Emotional states; Creative divergent thinking; Response inhibition; Heart rate variability; Skin conductance; Arousal

The role of territorial behavior in shaping user engagement on enterprise collaboration platforms - Lin, Lin; Morschheuser, Benedikt; Offergelt, Florian; Moser, Klaus (Proceedings of the 5th German Human Factors Summer School 2023, 2023)
The importance of ownership, control, and identification with specific resources is emphasized by organizations' territoriality theory (Brown et al., 2005; Pierce et al., 2003). Individual territorial behavior in enterprise collaboration platforms refers to employees actively taking ownership and providing or protecting information or ideas using platforms (Chen et al., 2022; Hobfoll, 1989). Supporting and acknowledging such conduct through collaboration platforms may foster user engagement by instilling a sense of autonomy, competence, and relatedness. This aligns with the Self-Determination Theory (SDT), which implies that people have fundamental psychological requirements for autonomy, competence, and relatedness. According to the notion, when these requirements are met, people are more intrinsically motivated and engaged (Ryan & Deci, 2000). Enterprise collaboration platforms' communication, coordination, cooperation, and content management functionality can help fulfill these psychological demands, thereby increasing user engagement. This paper explores the potential interaction between individual territorial behavior and the use of enterprise collaboration platforms, influencing the association between platform functionality, intrinsic need satisfaction, and user engagement. We conducted an empirical study with data from 170 employees from different organizations. Using Hayes' PROCESS in RStudio (Hayes, 2022; R Core Team, 2023; RStudio Team, 2023), we analyzed the link between platform functionality, intrinsic need satisfaction, and user engagement. The findings revealed an interaction effect and a mediating role of intrinsic need satisfaction in understanding the relationship between platform functionality, territorial behavior, and user engagement. The interaction effect between the usage frequency of platform functionality and territorial behavior of marking and defending was significant, suggesting that the relation between the use of platforms and intrinsic need satisfaction depended on the level of territorial behavior of marking and defending. When territorial behavior of marking and defending was low, higher use of platforms was associated with increased levels of intrinsic need satisfaction. However, when territorial behavior of marking and defending was high, higher use levels of platforms were associated with decreased intrinsic need satisfaction. Moreover, the indirect effects of usage frequency of platform functionality on user engagement through intrinsic need satisfaction were significant. The magnitude and direction of the indirect effects varied depending on the territorial behavior of marking and defending. Likewise, when territorial behavior of marking and defending was low, higher use levels of platforms were associated with increased user engagement through intrinsic need satisfaction. However, when territorial behavior of marking and defending was high, higher use levels of platforms were associated with decreased user engagement through intrinsic need satisfaction. In conclusion, employees showing lower territorial behavior of marking and defending were more likely to utilize the collaboration platform functionality of communication, coordination, cooperation, and content management in their work. This increased usage of platform functionality strengthened their intrinsic need satisfaction, fostering intrinsic motivation and enhancing user engagement. Our research contributes to understanding how individual territorial behavior, platform functionality, and intrinsic need satisfaction shape user engagement in intra-organizational collaboration. The results emphasize the importance of considering the interplay between territorial behavior and the use of platforms in fostering user engagement. These insights have practical implications for organizations seeking to optimize collaboration platforms to enhance employee engagement.<br